Pengembangan Sistem Monitoring Tingkat Salinitas Air Pada Tambak Rumput Laut Berbasis Website - Kamaruddin Kamaruddin; Andi Rosman N.; Baso Ali (Jurnal FisTa : Fisika dan Terapannya, 2023)
The level of salinity in water quality is one of the determining factors in the success of seaweed aquaculture production. The purpose of this study was to develop a website-based monitoring system for the level of water salinity in seaweed ponds. Monitoring system development is carried out by designing and developing an integrated website. Measurement of water salinity in ponds uses a sensor with a microcontroller connected via the internet network so that monitoring can be carried out without the need to go to the pond location. This type of research is development (Research and Development) which refers to the waterfall model (Planning, Analysis, Design, Implementation, Maintenance). The results of the research show that website development as a monitoring system has been successfully developed. There are four pages that can be displayed on the website for monitoring seaweed pond water salinity, namely the login page, homepage, viewing data, and monitoring water salinity. This research is expected to provide an overview in monitoring water quality in increasing the productivity of seaweed cultivation.